circWWC3 enhances the progression of triple-negative breast cancer by interacting with vimentin to regulate the secretion of CSF2 - Wu, Ming; Du, Yifan; Dong, Yuyang; Zheng, Yang; Gu, Lina; Tang, Xiaojun; Yan, Li; Ji, Hong; Sang, Yang; Liu, Fei (Frontiers in Immunology, 2025)
IntroductionCircular RNAs (circRNAs) have been reported to be important in the development and progression of breast cancer. Nevertheless, the biological functions and mechanisms underlying the action of circRNAs in triple-negative breast cancer (TNBC) remain poorly understood. The present study aimed to explore the role of hsa_circ_0001910 (also termed circWWC3) interacting with vimentin in regulating the secretion of Colony Stimulating Factor 2 (CSF2) and its effects on the malignant biological behavior of triple-negative breast cancer as well as the cytotoxic activity of NK cells.MethodsRNA-Seq was utilized to investigate potential circRNAs involved in five pairs of breast cancer (BC) tissues and their corresponding normal tissues. Fluorescence in situ hybridization (FISH) was conducted to verify the relationship between circWWC3 expression and patient clinical pathological parameters, as well as its intracellular localization. Gain- and loss-of-function assays were conducted to investigate the biological functions of circWWC3 in TNBC. A microarray analysis of mRNA expression profiles was conducted to explore the downstream target genes of circWWC3. RNA pull-down assays, RNA immunoprecipitation (RIP), and mass spectrometry were carried out to uncover the proteins interacting with circWWC3. Rescue experiments were performed to investigate the potential regulatory role of circWWC3 in the progression of TNBC in vivo and in virto.ResultsIn our present study, Circular RNA sequencing analysis revealed that the expression of circWWC3 was significantly upregulated in breast cancer (BC). FISH assay results indicated that circWWC3 is highly expressed in TNBC, and its elevated expression is associated with the patient’s T stage and lymph node metastasis, and it is primarily localized in the cytoplasm. The results of gain- and loss-of-function assays indicate that knockdown of circWWC3 significantly suppressed the proliferation, invasion, and migration of TNBC cells, while enhancing the killing efficiency of NK-92MI cells against TNBC cells. In contrast, overexpression of circWWC3 exhibited the opposite effects. The microarray analysis data indicated that CSF2 may be a downstream target of circWWC3. Interaction of circWWC3 with vimentin and their downstream target genes was confirmed by RNA pull-down, RIP, and mass spectrometry. Rescue experiments confirmed that vimentin knockdown partially counteracted the tumor-promoting effects of circWWC3. Further analysis revealed that circWWC3 upregulates CSF2 secretion mainly through its interaction with vimentin, a core component of the Epithelial-mesenchymal transition (EMT) signaling pathway, thereby facilitating the malignant progression of TNBC.ConclusionOverall, our findings reveal that elevated expression of circWWC3 serves a role in the malignant progression of TNBC by directly interacting with the S56 phosphorylation site of vimentin, an interaction that is associated with increased secretion of CSF2. Furthermore, circWWC3 emerges as a potential biomarker for breast cancer diagnosis and presents an attractive therapeutic target for the treatment of TNBC.